1991
DOI: 10.1090/qam/1121689
|View full text |Cite
|
Sign up to set email alerts
|

Pure torsion of compressible non-linearly elastic circular cylinders

Abstract: Abstract. The large deformation torsion problem of an elastic circular cylinder, composed of homogeneous isotropic compressible nonlinearly elastic material and subjected to twisting moments at its ends, is described. The problem is formulated as a two-point boundary-value problem for a second-order nonlinear ordinary differential equation in the radial deformation field. The class of materials for which pure torsion (i.e., a deformation with zero radial displacement) is possible is described. Specific materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Kirkinis and Ogden [9] derived conditions on the form of strain-energy function for which the isochoric deformation of pure torsion superimposed on a uniform extension can be supported with vanishing traction on the lateral surfaces of the cylinder, and pure torsion of a compressible isotropic elastic material was also examined in [10].…”
Section: Introductionmentioning
confidence: 99%
“…Kirkinis and Ogden [9] derived conditions on the form of strain-energy function for which the isochoric deformation of pure torsion superimposed on a uniform extension can be supported with vanishing traction on the lateral surfaces of the cylinder, and pure torsion of a compressible isotropic elastic material was also examined in [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Section 3, the constitutive model of interest, namely, the Blatz-Ko material, is briefly described. It is shown that the pure torsion solution of [1] is, in fact, the unique smooth radially symmetric solution for this material. The main results of the paper are contained in Section 4.…”
Section: Introductionmentioning
confidence: 94%
“…In particular, the analytic solution of a wide variety of problems in finite elastostatics for compressible materials has been possible for this material (see [8][9][10][11][12][13][14][15]1). Before proceeding in the next section to a discussion of implications of loss of ellipticity for pure torsion of the Blatz-Ko material (3.1), we show here that the pure torsion solution r(R) = R (3.3) obtained in [1,8,9] is, in fact, the unique smooth radially symmetric solution to the boundary value problem of concern. For the purpose of this proof, t it is convenient to take the cylinder radius to be unity (A = 1) and write the boundary value problem (see Eq.…”
Section: The Blatz-ko Materialsmentioning
confidence: 99%
See 2 more Smart Citations